The Impact of Using Financial Technology Services on Enhancing Financial Inclusion in the Digital Age: An Analytical Study of the Opinions of a Sample of Academics and Stakeholders in Commercial Banks in the Kurdistan Region - Mahmoud, Asst.L.Sawin Qadir Mahmoud; Al-Nuaimi, Prof. Dr. Basma Faleh Al-Nuaimi (Sulaimani Journal for Humanities, 2026)
This research aims to analyze the impact of using financial technology (FinTech) services on enhancing financial inclusion in Iraq amidst digital transformation, focusing on the Kurdistan Region as a model reflecting the reality of the Iraqi banking environment. The study employed a descriptive analytical approach, utilizing a field questionnaire distributed to a sample of 178 individuals, including academics and stakeholders from three commercial banks operating in the region. The questionnaire aimed to measure the relationship between FinTech services and the three dimensions of financial inclusion: access, use, and quality. Data analysis was conducted using the SPSS 27 statistical software, calculating means, standard deviations, correlation coefficients, and linear regression to assess the strength and direction of the relationship between the variables. The results showed a significant positive effect at the (0.05) significance level for the use of financial technology services in promoting financial inclusion in its three dimensions. It also showed that digital development contributes to expanding the customer base and improving the quality of financial services. Despite the continuation of some challenges related to security, trust and digital infrastructure, the research recommends the need to support the digital transformation of banking, develop financial legislation and policies, and promote digital culture among users in a way that contributes to achieving sustainable financial inclusion and economic growth in Iraq.
Keywords: Financial technology; financial inclusion; digital transformation